The Role of Cardiac Macrophage and Cytokines on Ventricular Arrhythmias - Chen, Mingxian; Li, Xuping; Wang, Songyun; Yu, Lilei; Tang, Jianjun; Zhou, Shenghua (Frontiers in Physiology, 2020)
In the heart, cardiac macrophages have widespread biological functions, including roles in antigen presentation, phagocytosis, and immunoregulation, through the formation of diverse cytokines and growth factors; thus, these cells play an active role in tissue repair after heart injury. Recent clinical studies have indicated that macrophages or elevated inflammatory cytokines secreted by macrophages are closely related to ventricular arrhythmias (VAs). This review describes the role of macrophages and macrophage-secreted inflammatory cytokines in ventricular arrhythmogenesis.